2021
DOI: 10.2139/ssrn.3773894
|View full text |Cite
|
Sign up to set email alerts
|

A 2D Porous Pb-MOF Based on 2-Nitroimidazole: CO <sub>2</sub> Adsorption, Electronic Structure and Luminescence

Abstract: A new porous metal-organic framework, [Pb 5 (Ac) 7 (nIm) 3 ] n (1), has been successfully synthesized by employing 2-nitroimidazole ligand and Pb 2+ ion. 1 contains novel the ribbon-shaped Pb-O SBU and reveals a 2D porous framework with a 1D tubular channel. Moreover, 1 shows moderate adsorption uptake towards CO 2 and luminescence properties from intraligand charge transfer. We further con rmed nitro group and metal ion are important adsorption sites by GCMC simulations, and the electronic structures of 1 was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
1
0
0
Order By: Relevance
“…The diffraction peaks observed in the Pb-MOF material are indexed at 9.9°, 10.6°, 10.8°, 14.2°, 18.6°, 19.8°, 22.6°, 26.6°, and 27.4°.(Fig. 4) The X-ray diffraction (XRD) pattern of the Pb-based metal-organic framework (MOF) obtained in this study is consistent with the findings reported in prior research 49,50 . Additionally, chemical structure of the Pb-MOF after stability test for 5 h of gas production.…”
Section: Resultssupporting
confidence: 90%
“…The diffraction peaks observed in the Pb-MOF material are indexed at 9.9°, 10.6°, 10.8°, 14.2°, 18.6°, 19.8°, 22.6°, 26.6°, and 27.4°.(Fig. 4) The X-ray diffraction (XRD) pattern of the Pb-based metal-organic framework (MOF) obtained in this study is consistent with the findings reported in prior research 49,50 . Additionally, chemical structure of the Pb-MOF after stability test for 5 h of gas production.…”
Section: Resultssupporting
confidence: 90%